KONTRIBUSI BPRS DALAM MEREALISASI FINANCIAL INCLUSION DI PEDESAAN: EVALUASI EMPIRIS DAN PENGUATAN STRATEGI - Hesi Eka Puteri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2015)
Islamic Rural Banking (populer as BPRS in Indonesia) is a kind of banking which conducts finance and loan especially in rural area. This monetary institution focuses to main function as a bank which gives the service to small and micro enterprises and based on Islamic principles in their operational system. By providing the fund to productive sectors, the economics will be tough and more competitive. That is why, this rural bank is also called “community bank”. In supporting financial inclusion -a concept where each person has a full access to monetary service, with competitive cost, convenience and prestige- the contribution of these community banks have really existed. On the other hand, the optimalization of this contribution process constraints to many things that covers internal and external problem. The finding of research recommends some strategies to improve the role of community bank in supporting financial inclusion in rural area, such as: reinforcement in regulation’s strategy, socialization’s strategy, competition’s strategy and human resource’s strategy Islamic Rural Banking (populer digunakan sebagai BPRS di Indonesia) adalah jenis perbankan yang melakukan pembiayaan dan pinjaman terutama di daerah pedesaan. Lembaga keuangan ini berfokus pada fungsi utama sebagai bank yang memberikan layanan untuk usaha kecil dan mikro dan berdasarkan prinsip-prinsip Islam dalam sistem operasional mereka. Dengan memberikan dana ke sektor produktif, ekonomi akan sulit dan lebih kompetitif. Itu sebabnya, BPR ini juga disebut